AI as Awakened Intelligence: Buddha, Kurzweil and the Film Her - Saxena, Neela Bhattacharya (Theology and science, 2020)
Fear of death, quest for permanence and desire to escape biology have been at the heart of many religions. Notions of technological singularity and AI posed by futurists like Ray Kurzweil touch upon that hunger. The historical Buddha, on the other hand, posited impermanence at the very heart of all existence. Focusing on the film Her, this paper will present AI as awakened intelligence. I would like to show that Alan Watts as a Zen master takes the emerging hyper-intelligent AI “Samantha” and others into a Buddhist Bardo, suggesting the possibility of AI as awakened intelligence beyond violence.